Social impact bonds as public policy : international panorama and contributions to implementation in Brazil - Sancho, Beatriu Canto (2022)
Despite being launched in 2011, the social impact bond (SIB) is an instrument under development that faces numerous challenges. This article presents the characteristics of SIBs and challenges related to their implementation as mechanisms to finance public projects with a social purpose. After a bibliographical and documentary review, three international cases of SIBs that have completed their maturity cycles, relevant for critical analysis of possible projects in Brazil, were selected. Ethical, methodological, metrics, results, and actor networks are analyzed in the three SIBs. Implications for projects in Brazil were considered from the analysis of these international cases.